Aspectos comportamentais e ecológicos do mico-leão-preto (Callitrichidae: Leontopithecus chrysopygus): uma revisão bibliográfica - Winter, Mariana Giuliatti [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Reptiles are ectotherm and depend on environmental heat sources to regulate body temperature (Tb). Increases or decreases on Tb cause variations on metabolic rates and are followed by heart frequency (fH) to meet the oxygen demand. Species that live in seasonal environments are subject to variations Tb and, therefore, in metabolism. The tegu lizard (Salvator merianae) is widely spread across South America and exhibits seasonal activity, characterized by an active period (August to April) and an inactive or estivation period (May to July). During the estivation period the metabolism suffers a depression and the oxygen consumption is lower even at similar Tb. This study aimed to compare the fH of Salvator merianae in two temperatures (17 oC and 25 oC) and in the two periods. The results showed a significant difference between the two temperatures analyzed. However, the difference between 17 oC and 25 oC was significant only during the dormancy period, indicating higher thermal sensibility during this period. Changes as the ones seen in this work let us suppose that sensorial neurons and the sympathetic nervous system trigger cardiovascular answers the same way as ectotherms...
Keywords: Ecologia animal; Primatas; Animais - Comportamento; Animal ecology